(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In 1500, Zakhiriddin Muhammad Babur met with Makhdumi Agzam Dahbedi, a prominent XVIth century spiritual leader, in Samarkand. He was a follower of the famous leader of the Sufi direction of Naqshbandiya in Central Asia Khoja Ahrar Wali. Historical materials show Babur’s close relationship with this sheikh. Subsequently, these mutual sincere relations continued until the very last days of Babur. In Makhdumi Agzam’s treatise "Risolai Boburiya" on Babur, Sheikh explains and comments on a number of theoretical concepts of the Naqshbandia. Babur has shown an interest in this spiritual teaching throughout his life and became its official representative in 1529/30. Key words–poetic style, tradition, interpretation,